Neuroprotective effect of edible bird’s nest in chronic cerebral hypoperfusion induced neurodegeneration in rats - Ismaeil, Rehab A.; Chua, Kien Hui; Ahmad Affandi, Khairunisa; Alallam, Batoul; Mohamed, Wael Mohamed Yousef; Mohd Noor, Mohd Fadly (OAE Publishing Inc., 2021)
Aim: Alzheimer’s disease (AD) is marked by insufficient blood supply to the brain, leading to progressive loss of memory and cognitive skills. The continuous reduction of cerebral blood flow resulting from chronic cerebral hypoperfusion leads to the overproduction of reactive oxygen species that triggers inflammation, causing cognitive decline. Till now, there is no cure for AD and the only option is symptomatic treatment. The current study evaluates the effect of edible bird’s nest (EBN) on hippocampal neurons, specifically in the CA1 hippocampal region, by using a rat model of chronic cerebral hypoperfusion-induced neuroinflammation.